THE LINGUISTIC LANDSCAPE OF PRINT ADVERTISEMENTS IN DAUGAVPILS: 1920–1930 - Pošeiko, Solvita (Via Latgalica, 2016)
The theme described in the title is connected with public advertising texts from two informational sources: newspapers printed in Daugavpils („Daugavas Vēstnesis” ‘The Daugava Herald’, „Daugavas Vārds” ‘The Daugava’s Word’, „Latgales Ziņas” ‘Latgalian News’ and „Latgales Vēstnesis” ‘The Latgale Herald”) and the linguistic landscape of the city, which characterizes the public information space. Commercial discourse is essential to this space, as a large part of public texts have the representation and promotion of establishments, companies and societies as a primary goal, in addition to the exhibition of offered goods and services.The aim of the article is to define and characterize from the perspective of linguistic landscape the tools and techniques used to represent businesses and establishments in Latvian print advertisements in the 1920s and 30s. In fulfillment of this goal, content analysis and the diachronic linguistic landscape approach has been used for data analysis and interpretation (Backhaus 2005, Pavlenko 2010, Pavlenko, Mullen 2015, Pošeiko 2015). For summarization of obtained results, the descriptive method has been used.Latvia is characterized in the interwar period by a unified language policy – including policies with mechanisms for the management of specific languages – highlighting the role of the Latvian language as the state language in the organization of public life and in nationalist ideology, and facilitating its use in all sociolinguistic functions. However, the interwar period in Latvia also marks the beginning of a period of Westernization – especially in the economic and cultural spheres – detectible in cinema, theater and concert posters; print advertisements for shops and consumer services, and business names in the urban environment.During this period newspapers were printed in Latvian, but some papers, calendars and journals were printed in Latgalian, Russian and Polish. Company names, advertisements and partially-legible posters are visible in period photographs of the linguistic landscape. Advertising information at the beginning of the 1920s is only to be found in Russian, or with bilingual Russian-Latvian texts. Monolingual language signs in Latvian – noticeably missing diacritic marks and appropriate word endings – only begin to be seen from the 1930s.